1997
DOI: 10.1002/(sici)1097-0142(19970601)79:11<2132::aid-cncr10>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased cathepsin D level in the serum of patients with metastatic breast carcinoma detected with a specific pro-cathepsin D immunoassay

Abstract: An increased level of cath-D in the serum of breast carcinoma patients is a late event observed only in patients with metastatic disease. This increased circulating level is more likely due to increased secretion of the proenzyme rather than to tumor cell lysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 13 publications
3
34
0
Order By: Relevance
“…The determination of CD and pCD in tissue and serum as an independent cancer prognostic marker has been suggested (Tandon et al, 1990;Brouillet et al, 1997). In the current study, we have confirmed secretion of pCD by HaCaT cells, cultured in serum-free media.…”
Section: Discussionmentioning
confidence: 99%
“…The determination of CD and pCD in tissue and serum as an independent cancer prognostic marker has been suggested (Tandon et al, 1990;Brouillet et al, 1997). In the current study, we have confirmed secretion of pCD by HaCaT cells, cultured in serum-free media.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have indicated a prognostic role for cath-D over-expression by reactive stromal cells [59][60][61][62]. Pro-cath-D is also increased in the plasma of patients with metastatic breast cancer [63,64], indicating that part of the pro-cath-D secreted by tumors can be released into the circulation. [65,66].…”
Section: Over-expression Of Cath-d In Breast Cancer Cellsmentioning
confidence: 99%
“…When antibodies specifically recognizing pCD have been used, two groups reported findings of elevated concentration of pCD in serum of metastatic breast cancer patients, 81,82 suggesting that, at least in final stages of cancer, pCD is released into the bloodstream. It is important that the activation peptide sequence is recognized by the immune system as a non-self-structure and triggers the production of specific antiactivation peptide antibodies.…”
Section: Cancer Gene Therapymentioning
confidence: 99%